Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.langmuir.6b01275
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Transitions of Droplets Wetting a Series of Triangular Grooves

Abstract: Morphology and thermodynamics of a microdroplet deposited on a grooved inhomogeneous surface with triangular cross section of the grooves were studied by computer simulations with the use of Surface Evolver program. With increasing volume of the droplet, it initially spreads along the series of grooves assuming the filament-like morphology. After reaching a certain volume, the surface wetted by the droplet is reduced and the droplet assumes the bulge morphology or spreads over the surface bordering on the groo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Grooves act as sinks that slow spreading perpendicular to the grooves because polymer is pulled along the grooves. Peaks can act to “pin” the polymer and inhibit spreading perpendicular to the grooves in agreement with previous research, , but this is a secondary mechanism that mainly affects spreading kinetics but does not significantly affect anisotropic spreading. By comparing two textures both with sinusoidal wave peaks, w / h = 2.00, and L = 15σ but one substrate with θ = 60° grooves and the other with sinusoidal wave grooves, we observe that d || increases by 136% and d ⊥ decreases by 27% when spreading on grooves with θ = 60°.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Grooves act as sinks that slow spreading perpendicular to the grooves because polymer is pulled along the grooves. Peaks can act to “pin” the polymer and inhibit spreading perpendicular to the grooves in agreement with previous research, , but this is a secondary mechanism that mainly affects spreading kinetics but does not significantly affect anisotropic spreading. By comparing two textures both with sinusoidal wave peaks, w / h = 2.00, and L = 15σ but one substrate with θ = 60° grooves and the other with sinusoidal wave grooves, we observe that d || increases by 136% and d ⊥ decreases by 27% when spreading on grooves with θ = 60°.…”
Section: Resultssupporting
confidence: 91%
“…The ability to create anisotropic spreading in particular, which enables liquid spreading to occur in a user-specified direction, finds application in micro/nanofluidics, flexible electronics, and drag reduction surfaces . Several research groups have shown both experimentally and numerically that unidirectionally textured substrates lead to anisotropic spreading, where liquids spread preferentially in the direction parallel to the texture. Anisotropic spreading on unidirectionally textured substrates is most commonly explained by texture peaks, which impose a mechanical barrier that effectively “pins” the three-phase (solid/liquid/gas) contact line of the spreading liquid, inhibiting spreading in the direction perpendicular to the texture. , The texture peaks are often described as energetic barriers that oppose wetting, which Yong and Zhang attribute to a high local atomic density at texture peaks, based on the results of molecular dynamics (MD) simulations (texture height of 1.85-23.77 Å). The liquid may be confined by texture peaks in the perpendicular direction and “squeezed” in the parallel direction.…”
Section: Introductionmentioning
confidence: 99%
“…14 More generally, static interfacial shapes of sessile liquid drops wetting chemical or topographic surface patterns have been widely studied both at the applied 15,16 and fundamental levels. 13,14,[17][18][19][20][21][22] Small drops wetting a rectangular stripe or annular ring, in particular, can be morphologically bi-stable in a certain range of liquid volumes. 14,23,24 In the latter cases, the interface of a drop in mechanical equilibrium may be found either in a flat, spread-out "channel" morphology or in a localized 3 .…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the static interfacial shapes of sessile liquid drops wetting the chemical or topographic surface patterns have been widely studied both at the applied , and fundamental levels. ,, Small drops wetting a rectangular stripe or annular ring, in particular, can be morphologically bistable in a certain range of liquid volumes. ,, In the latter cases, the interface of a drop in mechanical equilibrium may be found either in a flat, spread-out “channel” morphology or in a localized drop-like “bulge” morphology. Close to the point of instability, the energy barrier separating these two interfacial conformations is small, and one can expect that the transition from the metastable state into the global energy minimum can be easily triggered by external stimuli like mechanical vibrations of the underlying substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Raj et al designed micropillar arrays on the surface to tailor the droplet contact area into different shapes which yields asymmetric droplets. Others have used substrates with different cross-sectional shapes to frame the droplet into different geometries. While these studies provide practical solutions for maintaining an asymmetric droplet, a mechanistic understanding of the contact line pinning that shapes the droplet into a stable nonspherical form is still lacking. Retention of liquids on noncylindrical (i.e., asymmetric) pillar structures exhibit very different characteristics from the retention on a cylindrical pillar, where the apparent contact angle, θ a , varies along different radial directions and at different stages of the pinning.…”
Section: Introductionmentioning
confidence: 99%